Inhibition effects of benzalkonium chloride on Chlorella vulgaris induced corrosion of carbon steel. (15th April 2020) - Wang, Junlei; Zhang, Tiansui; Zhang, Xinxin; Asif, Muhammed; Jiang, Lipei; Dong, Shuang; Gu, Tingyue; Liu, Hongfang
Abstract: In this work, a surfactant, benzalkonium chloride (BAC), was used to study its effects on both the growth of Chlorella vulgaris and the corrosion caused by its biofilm. Experimental results indicated that BAC at a low concentration of 3 mg/L suppressed C. vulgaris growth and achieved 81 % corrosion inhibition based on weight loss reduction. The inhibition effects increased when the BAC dosage was increased. At 30 mg/L, the corrosion inhibition increased to 95 %. Electrochemical results supported surface pitting analysis, weight loss results data and confirmed the corrosion inhibition.